Coral like gadolinium doped hematite nanostructure as stable and robust electrocatalyst for oxygen evolution water splitting. (15th April 2023) - Un Nisa, Mehar; Gouadria, Soumaya; Houda, Sara; Jabbour, Karam; Manzoor, Sumaira; Aman, Salma; Najam-Ul-Haq, Muhammad; Naeem Ashiq, Muhammad
Highlights: A facile hydrothermal route was used to fabricated the Gd-doped Fe2 O3 . The optimized material showed low Tafel slope value of 48 mV/dec. Gd doped material also showed lower overpotential of 245 mV to achieve 10 mA/cm 2 current density. 10% doping of Gd showed excellent stability up to 50 h. Abstract: Due to the slow four-electron transference, the electrocatalytic oxygen evolution reaction (OER) is less effective at water splitting. Therefore, it is imperative to fabricate OER electrocatalysts that are highly active, durable, and scalable. Using in-situ hydrothermal growth, we preliminary grow hematite, and further gadolinium is doped on the already prepared iron oxide (Fe2 O3 ) catalyst layer on the exterior of nickel foam (NF). This is done to produce a coral-like structure in three dimensions. According to electrochemical studies, the optimized Gd-Fe2 O3 catalyst outperforms electrocatalytic OER catalysts as it requires only 245 mV to achieve 10 mA/cm 2 current density, has a smaller Tafel slope (48 mV/dec) and is stable (10 mA/cm 2 @50 h). The enhanced electrocatalytic performance results from coral-like three-dimensional shape that exposes more active sites and higher surface area. Future nanostructured novel catalysts for OER can be intelligently designed using the simple method employed in this study.